Física y química: Bachillerato 2 / J. M. Dou. M. D. Masjuan. N. Pfeiffer - Dou, J. M. Masjuan, M. D. Pfeiffer, N. (1976)
Trata de dar a conocer la naturaleza de la ciencia, la historia de la física y de la química.